2017
DOI: 10.3390/economies5040046
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Variance of the Effects of a Project’s Location on Key Issues and Challenges in Post-Disaster Reconstruction Projects

Abstract: After a disaster, the reconstruction phase is driven by immediate challenges. One of the main challenges in the post-disaster period is the way that reconstruction projects are implemented. Reconstruction cannot move forward until some complex issues are settled. The purposes of this research are to highlight the issues and challenges in post-disaster reconstruction (PDR) projects and to determine the significant differences between the issues and challenges in different locations where PDR projects are carrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…P value of the contact time and dosage are less than 0.05. Their f value is also high, which is an indication that the contact time and adsorbent dosage have a significant effect on the percentage removal of Cr (VI) from textile effluent; for pH, the P value is higher than 0.05 and the f value is low, which shows that the factor is not statistically significant (Elleta et al., 2018; Brereton, 2018, Zhou, & Skidmore, 2017; Ismail et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…P value of the contact time and dosage are less than 0.05. Their f value is also high, which is an indication that the contact time and adsorbent dosage have a significant effect on the percentage removal of Cr (VI) from textile effluent; for pH, the P value is higher than 0.05 and the f value is low, which shows that the factor is not statistically significant (Elleta et al., 2018; Brereton, 2018, Zhou, & Skidmore, 2017; Ismail et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The ineffective management of these challenges may lead to ineffective delivery of the projects and hamper the intended outcomes. The challenges as studied by various authors are: following regulations related to the construction of Project Moloney (2014), Boen (2006), Nazara and Resosudarmo (2007) Moe and Pathranarakul (2006), rising costs of materials and labour Hidayat and Egbu (2010), Ismael et al (2017). The challenges are in meeting the needs of the sudden increase in labour, and the fact that local natural resources are in scarce supply (e.g.…”
Section: Challenges For Managing Pdrpsmentioning
confidence: 99%
“…Post disaster reconstruction directly affected by the location of the destructed area due to its effects on the funding amount, less in the technical manpower and resources [2]. While the community participation has a major role in the process of housing reconstruction after the disaster, it had become necessary to focus on it and collect more information about it when reconstruct [10].…”
Section: Background Of Studymentioning
confidence: 99%
“…Anyway, the barriers of the post disaster reconstruction are everywhere, but the differences are in the type of challenges. Ismail, et al [2] showed that community participation, assessment, funding and quality of work are the main challenges of the post disaster reconstruction in many countries around Indonesia. That's why some development plans should be prepared for such disasters insect, some temporary construction should be done after catastrophes to help people to have some settlement [3].…”
Section: Introductionmentioning
confidence: 99%